PENGARUH TEKNOLOGI KOMUNIKASI TERHADAP MINAT BACA MAHASISWA TADRIS BAHASA INDONESIA UIN SU MEDAN - Hasibuan, Nisa Hafzhiyah; Audina, Fitra; Marpaung, Ayu Anggreini; Fadillah, Mutia Asmi; Dalimunthe, Winda Vita Puri (Program Studi Pendidikan Bahasa Indonesia, Institut Pendidikan Nusantara Global, 2023)
This research focuses on explaining how communication technology influences the reading interest of Indonesian language students at UIN SU Medan. Communication technology among teenagers or students greatly influences their interest in reading, especially students who use communication technology such as smartphones or the internet are more interested because apart from that they can access content or features that are considered more interesting than reading books. The research method used is causal associative (influence) research using a quantitative approach. The aim of this research is to determine the significant influence of Communication Technology on reading interest of Indonesian Tadris Language Students at UIN SU Medan. The results of the research are the influences caused by the current development of communication technology, communication technology certainly has both positive and negative impacts on its users. Keyword: Influence of technology, communication, student reading interest